Pengaruh Pasar Minggu Terhadap Perekonomian Masyarakat di Kabupaten Sekadau - Adil Bertus; Florentina Neneng Sabela (Hunatech Vol. XXX, No. XXX, 2023)
This study aims to determine the influence of the Sunday market on the economy of the people in Sekadau Regency. This research focuses on the high interest of the people in Sekadau Regency to trade and shop at the Sunday market which sells various local products. These conditions make the authors interested in conducting research to find out why people prefer to trade and shop at the market that week. The results of this study are that the Sunday market located in Sekadau City also adds employment opportunities for the surrounding community, the people of Sekadau Regency, the majority of whom work as farmers and gardeners, because of the Sunday market, apart from being farmers or planters, the community can also become traders. In addition, farmers or planters who focus on expanding agricultural land or plantations can look for employees to help manage the garden and help sell products. Keywords: Market, Sunday, Economics, People, Sekadau